Influência de sais de cálcio nas propriedades anticorrosivas de revestimentos híbridos siloxano-p(HEMA) sobre a liga Ti-6Al-4V para implantes biomédicos - Almeida, Larissa de Lima (2020)
The Ti-6Al-4V alloy in contact with the body fluid for a long period has low wear resistance, and allows the release of Aluminum and Vanadium ions that can cause adverse reactions in tissues and neurological disorders. Organic-inorganic coatings, based on poly (2-hydroxyethyl methacrylate) with calcium addition, can be an alternative to solve these problems. Initially, the formation of hybrids was studied using the following techniques: nuclear magnetic resonance (NMR), Fourier transform infrared spectroscopy (FTIR), low angle X-ray scattering (SAXS) and thermogravimetric analysis (TG), and it was observed that the addition of the CaSO4 and Ca3(PO4)2 salts to the hybrid matrix promoted an increase in the degree of hydrolysis and condensation favoring the formation of more regular polymer chains. The morphological tests showed that the coatings with addition of CaSO4 and Ca3(PO4)2 showed homogeneity, absence of cracks, and the formation of low thickness coatings, with adhesion to the substrate, hydrophobic and with some micro-roughnesses, according to roughness tests made by atomic force microscopy. Electrochemical tests in simulated body fluid monitored by electrochemical techniques indicated greater resistance to corrosion for hybrid coatings SH 2X compared to uncoated alloy. The film without the addition of calcium salt proved to be more resistant during the entire immersion time due to the more compact silica mesh, since the coating with the addition of calcium phosphate showed better resistance to corrosion at the end of the test, relative to the layer compaction due formation of corrosion products. In this work, we sought to produce a coating that presents a balance between biological and anti-corrosion properties and that has elements that promote biocompatibility and bioactivity without compromising corrosion resistance.